2015
DOI: 10.3390/ijerph120911178
|View full text |Cite
|
Sign up to set email alerts
|

High Birth Weight Increases the Risk for Bone Tumor: A Systematic Review and Meta-Analysis

Abstract: There have been several epidemiologic studies on the relationship between high birth weight and the risk for bone tumor in the past decades. However, due to the rarity of bone tumors, the sample size of individual studies was generally too small for reliable conclusions. Therefore, we have performed a meta-analysis to pool all published data on electronic databases with the purpose to clarify the potential relationship. According to the inclusion and exclusion criteria, 18 independent studies with more than 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…In addition, recent studies have also revealed positive associations between birth weight and various types of cancers. Exemplary birth weight-associated cancers include renal cell cancer (Bergstrom et al, 2001), colorectal cancer (Sandhu et al, 2002), primary central nervous system tumor (Georgakis et al, 2017), prostate cancer (Zhou et al, 2016), bone tumor (Chen et al, 2015), and breast cancer (Xu et al, 2009). However, it remains unclear whether the identified associations between birth weight and the aforementioned adult diseases represent truly causal relationship, or are merely spurious associations caused by common confounding factors that occur during prenatal life (Barker, 1990; Leon, 1998; Law, 2002; Ruiz-Narvaez et al, 2014; Kahn et al, 2017) or confounding due to pleiotropy and shared genetic components (Lawlor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have also revealed positive associations between birth weight and various types of cancers. Exemplary birth weight-associated cancers include renal cell cancer (Bergstrom et al, 2001), colorectal cancer (Sandhu et al, 2002), primary central nervous system tumor (Georgakis et al, 2017), prostate cancer (Zhou et al, 2016), bone tumor (Chen et al, 2015), and breast cancer (Xu et al, 2009). However, it remains unclear whether the identified associations between birth weight and the aforementioned adult diseases represent truly causal relationship, or are merely spurious associations caused by common confounding factors that occur during prenatal life (Barker, 1990; Leon, 1998; Law, 2002; Ruiz-Narvaez et al, 2014; Kahn et al, 2017) or confounding due to pleiotropy and shared genetic components (Lawlor et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Birthweight is an additional factor undergoing investigation in epidemiologic studies of osteosarcoma . Higher birthweight is indicative of increased fetal growth in utero , and potentially, greater exposure to insulin‐like growth factors (IGFs).…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14][15] Birthweight is an additional factor undergoing investigation in epidemiologic studies of osteosarcoma. 2,6,16 Higher birthweight is indicative of increased fetal growth in utero, and potentially, greater exposure to insulin-like growth factors (IGFs). High birthweight has previously been linked to increased risk of a variety of childhood cancers including acute lymphoblastic leukemia, Wilm's tumor, neuroblastoma, non-Hodgkin's lymphoma, soft tissue sarcomas, and germ cell tumors.…”
Section: Introductionmentioning
confidence: 99%
“…To assess the potentialfor unmeasured confounding, a leave-one-out sensitivity analysis was completed ( Chen et al, 2015 ; Hernán & Robins, 2020 ; Noyce et al, 2017 ; Zeng, Yu, & Xu, 2019 ). This analysis was employed to determine the degree of potential confounding added to the analysis by removing—and no longer controlling for—each of the covariates.…”
Section: Methodsmentioning
confidence: 99%